Association between inter-limb asymmetry and athletic performance tasks: a season long study in elite academy soccer players - Bishop, C.; Read, P.; Chavda, S.; Turner, A. (The Journal of Strength and Conditioning Research, 2021)
Purpose: Despite numerous empirical investigations recently reporting associations between asymmetry and reduced athletic performance, all of these have been conducted for a single time point only, with no study to date investigating this notion longitudinally. Thus, the aims of this study were to determine the association between asymmetry and measures of speed and change of direction speed (CODS) performance throughout a competitive soccer season and, determine whether any observed changes in asymmetry were associated with changes in speed and CODS performance. Methods: Eighteen elite male under-23 academy soccer players performed unilateral countermovement jumps, unilateral drop jumps (DJ), 10- and 30-m sprints, and 505 CODS tests at pre, mid, and end of a competitive season. For the unilateral countermovement jump, recorded metrics included: jump height, peak force and concentric impulse. For the unilateral drop jump, recorded metrics included: jump height, ground contact time and reactive strength index. Data was assessed for normality and showed test scores to be normally distributed, but asymmetry to be non-normally distributed. Reliability data (CV and ICC) were calculated at each time point, with repeated measures and Friedman's ANOVA's used to determine systematic bias for test data and asymmetry scores, respectively, between time points. Spearman's correlations were used twice: (a) to determine the association between asymmetry scores and speed/CODS data at each time point and, (b) to determine the association between changes in asymmetry (as a percentage) and changes in speed/CODS scores (as raw test scores), between time points. For correlations, Bonferroni corrections were applied to account for multiple comparisons and the familywise type 1 error rate, resulting in statistical significance being set at p < 0.008. Results: No significant relationships were evident during pre-season or mid-season between asymmetry and speed or CODS performance. However, significant correlations were shown at the end of season between DJ height asymmetry and 10-m sprint time (r = 0.62; p = 0.006) and 505 time on the right limb (r = 0.65; p = 0.003). No significant correlations between changes in asymmetry and changes in speed or CODS were evident at any time point. Conclusions: Although numerous studies have reported associations between asymmetry and reduced athletic performance, it seems that these associations with speed and CODS do not track consistently over time. Thus, suggestions for the reduction of asymmetry that may indirectly enhance athletic performance cannot be made. This is likely explained by the highly variable nature of asymmetry in the present study, which showed no consistent pattern in 'increase or decrease of asymmetry' throughout the season for any of the 18 players. Practical Applications: Despite the recent evidence that asymmetry may be indirectly harmful to measures of athletic performance, this is the first data to determine these relationships longitudinally and they do not support this viewpoint. Thus, practitioners are advised to use raw test data to help guide their decision-making throughout a competitive soccer season, instead of ratio data such as asymmetry. If between-limb differences are to be assessed, it is possible that quantifying the absolute difference between limbs, may be more useable than a relative value, such as a percentage. However, further research into this line of investigation is warranted to fully corroborate this suggestion.